Pronera em Roraima: para al??m da regula????o social - Ximenes, Jedson Machado (2016)
The National Education Program at the Agrarian Reform (PRONERA) is a milestone in the construction and consolidation of public policies for the access of the peasant population to education, allowing the insertion of settlers into the literate world. This research aims to make a critical analysis of the history and the reality and the perspective of Pronera's performance in the state of Roraima. This research drew on the dialectical method proposed by Gramsci to understand the history of that program???s educational activities in Roraima in its relation with the economic, political, social and cultural context. The data was obtained from primary documents such as: the Constitution of the Federative Republic of Brazil; Guidelines and Bases of National Education Law - which regulates the standards of education in the country; Operational Guidelines for Basic Education in Rural Schools; National Policy of Rural Education and National Education Program in Agrarian Reform decrees; and Pronera???s Operation Manual. In addition to that, data was collected using personal interview as instrument with subjects that acted directly on projects in Roraima state, including the insurers of Pronera, the National Institute of Colonization and Agrarian Reform - INCRA superintendent, deans, extension provosts, general coordinators, pedagogical and local coordinators, students and teachers. The results showed that the Pronera has many obstacles to overcome in order to provide an education based on social justice, integral formation of the settlers and development of the field, among which we can mention the lack of infrastructure in the settlement projects, low training of teachers, long distances from classrooms and insufficient financial resources to ensure the regularity of the various forms of education. In the broad context, it is clear that the education offered by the program is merely a social regulation form, keeping things as they always have been, that being, the overlapping of the dominant ideology interests of the country "dressed up" as a promise of social justice.